Principles of electrical machine design - Agarwal, R.K (S.K. Kataria & sons, 1997)
Principles of electrical machine design / Agarwal, R.K.. -- New Delhi: S.K. Kataria & sons, 1997 621.31042 Ag261e3 No. of Copies : 1